Physical Education and Sports Course: The Content Analysis - Mustafa BEHLÜL; Çağda KIVANÇ ÇAĞANAĞA (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Physical education plays an important role in improve students’ health. Therefore, the main objective of the present study is to examine the PhD level and Masters level thesis submissions and dissertations that are related to physical education and sports studies in the context of Turkey. To this end, the researcher conducts a content analysis. For the present study, a regional scanning model was applied in which 58 PhD and Masters level dissertations are selected. These dissertations are part of Turkey’s Higher Education Institution’s dissertations database and have been examined in terms of the year, institution, research model, method, data collection instrument, department, research topic, sampling group and applied education level. In the present study, pie charts and frequency tables have been used to illustrate the results of the data. It is shown that these quantitative methods have been mostly used in the dissertations written between 2015 and 2020, while qualitative methods have been used to a lesser degree. The present study makes significant contributions in terms of enriching the theoretical and managerial perspectives on the subject.